2017
DOI: 10.1128/genomea.00925-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Four Extensively Drug-Resistant Pseudomonas aeruginosa Strains, Isolated from Adults with Ventilator-Associated Pneumonia at a Tertiary Referral Hospital in Mexico City

Abstract: Four extensively drug-resistant Pseudomonas aeruginosa strains, isolated from patients with pneumonia, were sequenced using PacBio RS-II single-molecule real-time (SMRT) technology. Genome sequence analysis identified great variability among mobile genetic elements, as well as some previously undescribed genomic islands and new variants of class 1 integrons (In1402, In1403, In1404, and In1408).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“… 19 The ST found in this study has already been reported in different parts of the world 45 and the ST308 in Mexico. 46 So this is the first report that shows the presence of ST167 and ST385 in Mexico.…”
Section: Discussionmentioning
confidence: 78%
“… 19 The ST found in this study has already been reported in different parts of the world 45 and the ST308 in Mexico. 46 So this is the first report that shows the presence of ST167 and ST385 in Mexico.…”
Section: Discussionmentioning
confidence: 78%
“…Shading denotes regions of homology (nucleotide identity ≥95%). The accession number of Tn 6877 ( Espinosa-Camacho et al, 2017 ) used as reference is CP021775.…”
Section: Resultsmentioning
confidence: 99%
“…Region and bla VEB-3 Region Tn6877 (55.9 kb in length) was used as the prototype IME and initially found in P. aeruginosa Pa58 (Espinosa-Camacho et al, 2017). Tn6877, Tn6878, and a presumed primordial Tn6877related element were all integrated at the same site between the two chromosomal genes orf2892 (a subunit of ribonucleotide reductase) and orf1248 (ß subunit), and they had essentially identical backbones, which was 21.6 kb in length and contained attL/R and two different int genes ( Figure 6).…”
Section: Comparison Of Two Related Imes Tn6877 and Tn6878 And Their Dmentioning
confidence: 99%